Human rights, citizenship and dementia care nursing. (16th February 2012) - Kelly, Fiona; Innes, Anthea
<x xml:space="preserve">Abstract</x> Background. Human rights and citizenship are concepts widely used in health and social care literature. However, they are applied less frequently and less rigorously in dementia care. This paper briefly presents these concepts before exploring how they have been applied to dementia care policy and practice. We highlight areas of dementia care where human rights can be violated and citizenship can be denied. We suggest reasons why people with dementia can be denied their human and civil rights and discuss how such concepts provide a way to address cultural and practice change in dementia care. Aims and objectives. To demonstrate how these concepts can be used to challenge and improve dementia care nursing. Conclusions. This paper contributes to emerging discussion about dementia care nursing by challenging conventional ways of understanding dementia and the care practices that result. Taking a rights‐based approach allows nurses to examine inequity in services and address poor practice. Implications for practice. Looking at dementia through the lenses of citizenship and human rights provides a way to broaden the scope of contemporary dementia care nursing, to enable nurses to challenge inequity and to develop and improve the direct nursing care offered to people with dementia.